THE APPLICATION OF WORD ASSOCIATION GAME IN IMPROVING STUDENTS’ VOCABULARY MASTERY AT THE SECOND GRADE STUDENT OF SMPN 5 PUJUT - Terasne Terasne; Tawali Tawali; Nur Afriani (Mandala, 2018)
This research is aimed to know how to applycation of Word Association Game in improving students’ vocabulary mastery at the second grade students of SMPN 5 Pujut in academic year 2016/2017. This study focused on two statement of the problem, that are 1. Is Word Association Game able to improve students’ vocabulary mastery at the second grade students of SMPN 5 Pujut, and 2. What are the students perception towards the use of Word Association Game in improving students vocabulary mastery at the second grade students of SMPN 5 PUJUT.The method of this research used quantitative and qualitative method in the from of CAR. The data were gathered througsh quantitative and qualitative data. The quantitative data indicate students’ vocabulary score of pre test and post test and the result of questionnaire of students perception. Then the techniques which were used to collect the data were vocabulary test wich consisted of 25 items with 4 options of answere multiple choiches and limited responds. The finding of this study showed that there was improvement on the students’ vocabulary mastery. It could be seen from the mean score of pre test was 60, 26 and class that percentage was 26% and the mean score of post test was 82, 43 and class presentage was 82% indicating the target of 76 of the KKM 76 had been achieved. Based on the result persentage data in questionnaire such as SS was 75%, S was 13%, TT was 11%, TS was 0%, and STS was 0%. The results of the quastionnaire shows that students respons is very good.